Size Study of Sand Grain in the Aroen Meubanja Turtle Conservation Area, Aceh Jaya - Wahyuni, Sri; Bahri, Samsul; Nufus, Hayatun; Mursawal, Asri (Tropical Marine Environmental Sciences, 2025)
Due to its unique coastal characteristics, the Aroen Meubanja Turtle Conservation Area in Aceh Jaya has significant potential as a nesting site for sea turtles. This study analysed the area's sand grain size and characteristics to determine its suitability for turtle nesting. The research was conducted in March 2024, with sand samples collected from three stations using purposive random sampling. Laboratory analysis included sieving and sand grain classification based on size and shape using the Wentworth and Powers classifications. The Wentworth scale is used to classify grain size, while the Powers scale assesses the shape and roundness of the grains. The results revealed that over 70% of the sediment in the area consists of very fine sand, which is highly favourable for turtle nesting. The roundness of the sand grains indicates a long transportation process, contributing to their suitability for nesting. Fine sand allows for proper water drainage, preventing waterlogging in nests and maintaining optimal temperatures for egg incubation. Additionally, environmental factors such as beach width, slope, substrate temperature, humidity, and coastal vegetation further enhance the area's potential as a turtle conservation site. This study concludes that the Aroen Meubanja coastal area meets the criteria for an ideal turtle nesting habitat. Recommendations include habitat management, community education, and further research to ensure sustainable conservation efforts